EFEK MODERASI IKLIM KELAS PADA PENGARUH MOTIVASI BELAJAR TERHADAP HASIL BELAJAR SISWA (SYSTEMATIC LITERATURE REVIEW) - Nada Minel Safitri, - (2021)
Penelitian ini mengulas beberapa artikel tentang motivasi belajar yang dianggap berpengaruh dalam peningkatan hasil belajar, serta iklim kelas yang dianggap berpengaruh memperkuat pengaruh motivasi belajar terhadap hasil belajar siswa. Tujuan penelitian ini untuk mengetahui pengaruh motivasi belajar terhadap hasil belajar siswa, serta efek moderasi iklim kelas pada pengaruh motivasi belajar terhadap hasil belajar siswa. Pencarian artikel relevan dilakukan pada publikasi online seperti Semantic Scholar, Springer, APA PsycNet, Taylor&Francis, ResearchGate, Elsevier, Frontiers in Psychology, European Journal of Education Studies, International Journal of Economic Studies, Jurnal Tunas Pendidikan, Economic Education Analysis Jurnal, Jurnal Pendidikan Matematika, Eurasia Jurnal, yang diterbitkan antara tahun 2010-2020. Penulis memperoleh 12 artikel yang memenuhi syarat berdasarkan karakteristik pemilihan artikel relevan yang telah ditentukan. Temuan artikel menunjukan bahwa motivasi belajar berpengaruh positif terhadap hasil belajar siswa. Selain itu, ditemukan bahwa iklim kelas dapat memperkuat pengaruh motivasi belajar terhadap hasil belajar siswa. Hal ini disebabkan karena ketika yang dirasakan oleh siswa berupa iklim kelas positif, hal tersebut dapat mendukung siswa lebih semangat belajar, sehingga motivasi belajar akan semakin kuat, pada gilirannya akan meningkatkan hasil belajar siswa. Kata kunci: Motivasi Belajar, Hasil Belajar Siswa, Iklim Kelas. Nada Minel Safitri (1601884). "The Moderating effect of Classroom Climate on the Impact of Learning Motivation Toward Student Learning Outcomes (Systematic Literature Review)". Under Supervisor I: Dr. H. Dadang Dahlan, M.Pd. and Supervisor II: Dr. Siti Parhah, S.Pd., M.SE. ABSTRACT This study reviews several articles about learning motivation that are considered influential in improving learning outcomes, as well as classroom climate which is considered influencing the influence of learning motivation on student learning outcomes. The purpose of this study was to determine the effect of learning motivation on student learning outcomes, as well as the moderating effect of classroom climate on the effect of learning motivation on student learning outcomes. Search for relevant articles was carried out on online publications such as Semantic Scholar, Springer, APA PsycNet, Taylor & Francis, ResearchGate, Elsevier, Frontiers in Psychology, European Journal of Education Studies, International Journal of Economic Studies, Jurnal Tunas Pendidikan, Economic Education Analysis Journal, Journal of Mathematics Education , Eurasia Journal, published between 2010-2020. The author obtained 12 articles that meet the requirements based on the characteristics of the selection of relevant articles that have been determined. The findings of the article show that learning motivation has a positive effect on student learning outcomes. In addition, it was found that the classroom climate can strengthen the influence of learning motivation on student learning outcomes. This is because when students feel a positive classroom climate, it can support students to be more enthusiastic about learning, so that learning motivation will be stronger, in turn it will improve student learning outcomes. Keywords: Learning Motivation, Student Learning Outcomes, Classroom Climate.